THE VARIOUS FACTORS OF SUPPORTING AND INHIBITING THE IMPLEMENTATION OF CHARACTER EDUCATION (Study at Madrasah Aliyah Negeri 1 Mamuju) - Wahyun, Wahyun; Rama, Bahaking; Susdiyanto, Susdiyanto; Achruh, Andi (Jurnal Diskursus Islam, 2021)
This article examines the various factors supporting and inhibiting the implementation of character education in Madrasah Aliyah Negeri 1 Mamuju. The background of this research is the importance of character education to shape students’ character as a solution to moral damage and the threat of national disintegration. This research is descriptive qualitative, with a phenomenological approach. The data sources of this research are primary and secondary data. Primary data was taken from the stakeholders of MAN 1 Mamuju through interviews. Meanwhile, secondary data were taken from documents and literature related to this research. The main instrument is the researcher himself as the key instrument, while the interview guide, observation and documents are complementary instruments. The analysis used is data reduction, data presentation and conclusion drawing. The results obtained in this research are strategic supporting factors, namely planning, control and evaluation, and operational ones, namely the availability of professional educator resources. In contrast, the inhibiting factors are student discipline and limited facilities owned.